Coffee Shop Culture: Urban Lifestyle Transformation in the Perspective of Consumerism - Mario Mario (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research departs from the phenomenon of the mushrooming of coffee shops in Makassar, which significantly affects the pattern of activities and social interactions of urban communities. Coffee shops are now an inseparable part of urban life, creating new spaces that are full of symbolic meaning. This research aims to reveal how the transformation of urban people's lifestyles occurs through the existence of coffee shops as public spaces. The approach used in this study is a qualitative method with a descriptive type, which aims to provide an in-depth picture of this phenomenon through case studies on several coffee shops that represent these characteristics. The results of the study show that coffee shops not only function as a place to enjoy drinks, but also as a public space that reflects the social and cultural identity of the community. The existence of coffee shops creates a symbol of prestige for its visitors, which indirectly makes hanging out in coffee shops an indicator of certain social status. This is closely related to the hedonistic lifestyle, where individuals are willing to spend time and money just to hang out in order to strengthen their self-image in front of the public. In addition, this study also found that coffee shops have become an arena for lifestyle expression influenced by advertisements and trends, where visitors feel the need to adjust their appearance, including wearing clothes that are popular in the latest fashion trends, in order to maintain the existence and social credibility in their environment. Thus, coffee shops in Makassar are not only a place of recreation, but also a social phenomenon that reflects changes in the lifestyle of urban people, which are influenced by aspects of prestige, consumerism, and popular culture dynamics. This research contributes to understanding the role of public spaces such as coffee shops in shaping the lifestyle of modern urban communities.